Trans-disciplinarity in tourist studies: La Trans-disciplinariedad en los Estudios Turísticos. - Korstanje, Maximiliano E. (2016)
Numerous tourism related researchers are concerned on the lack of consolidation of their discipline to be considered seriously by other academic circles. This is the main aspect of discussion of this essay review. Unlike the whole conceptual studies, it is held the thesis that there are structural reasons, which are enrooted in the advance of post modernism as the main relevant cause of knowledge-led fragmentation. As a result of this, tourism research has not consolidated as a maturated epistemology.